Online sequential extreme learning machine for classification of Mycobacterium tuberculosis in Ziehl-Neelsen stained tissue - Muhammad Khusairi, Osman; Mohd Yusoff, Mashor, Prof. Dr.; Hasnan, Jaafar, Assoc. Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/